Downtime Reduction with Fast Restart Function in a Beverage Production System - Chaiyan Jettanasen; Natthanon Phannil; Suntiti Yoomak; Surakit Thongsuk; Sulee Bunjongjit; Atthapol Ngaopitakkul (Processes, 2022)
Bottled-beverage production systems require considerable machinery and sophisticated control systems. A malfunction in the production system can result in machine stoppages, thereby decreasing productivity and resulting in the production output not meeting the required target. Therefore, the problem of frequent stoppages of the production system must be resolved. The ‘Fast Restart Function’ is a proposed feature that can help reduce machine downtime by decreasing the time required for the product to drain from the conveyor. In this study, using this strategy, the investigated manufacturing system’s efficiency increased from 86.81% to 90.29%, enabling an increase in the average production capacity by 27,187 bottles per day, i.e., a 3.48 percent increment of the daily capacity. When employed in inefficient production systems or systems facing frequent shutdowns, this system is of considerable value for mitigating production stoppages.
Keywords: Advanced Manufacturing and Logistics Optimization; Manufacturing Process and Optimization; Scheduling and Optimization Algorithms